Tactics and Strategy for the SEAP - Action Plan for Sustainable Energy. The city of Alessandria as a case study - Savio, Lorenzo (TECHNE - Journal of Technology for Architecture and Environment, 2014)
The European Union has included, since 2007, in its Plan for Energy Efficiency, a specific action addressed to the Cities: the Covenant of Mayors. The initiative involves directly the Mayors, who, signing a document of adhesion, will commit to go beyond the EU target of CO2 reduction, implementing a SEAP: Strategic Energy Action Plan. The SEAP is an innovative planning tool, which allows the city to build an overall scenario for reducing CO2 emissions, with actions belonging to different sectors. In all the steps following the signing of the Covenant (adoption, monitoring, updating the SEAP) it is crucial, for the city, to adopt an effective coordination, able to put a system not only the social actors with key roles, but also all the past experiences, the best practices, demonstration projects and everything which, in the local context, can be con- sidered strategic for a sustainable urban regeneration. In Italy, the Covenant had a considerable success, with more than 1,800 cities, the 55% of the total in Europe. The city of Alessandria can be considered an interesting case study, because the SEAP development was integrated to the European Demonstrative Project Concerto AL Piano, aimed at the regeneration of a urban district, making it sustainable from the energy consumption point of view. The research group of Politecnico di Torino supported Alessandria in all the process.